Effect of annealing temperature on properties of WS2 thin films. (3rd April 2022) - Ye, Wei; Du, Pengfei; Xiao, Sheng; Li, Mengfei
ABSTRACT: In this paper, the influences of different annealing temperature from 200 to 500°C with an interval of 100°C on the properties of WS2 thin films deposited onto the Si substrates and glass substrates prepared through RF magnetron sputtering were investigated. The optical and electrical properties were tested using Ultraviolet Spectrophotometer and Hall Tester, respectively. The results show that the properties of WS2 thin films did not change linearly with temperature, WS2 thin films obtained the optimal electron mobility of 1.69 × 10 3  cm 2 /Vs, the optimal bulk carrier concentration of 1.28 × 10 18  cm −3, the smallest band gap of 1.5 eV, and the smallest resistivity of 5.77 × 10 −2 Ω −1 ·cm −1 at 400°C. Moreover, the S/W was close to the ideal WS2 stoichiometric of 2.